Forward genetic approaches for elucidation of novel regulators of Lyme arthritis severity - Bramwell, Kenneth K.C.; Teuscher, Cory; Weis, Janis J. (Frontiers in Cellular and Infection Microbiology, 2014)
Patients experiencing natural infection with Borrelia burgdorferi display a spectrum of associated symptoms and severity, strongly implicating the impact of genetically determined host factors in the pathogenesis of Lyme disease. Herein, we provide a summary of the host genetic factors that have been demonstrated to influence the severity and chronicity of Lyme arthritis symptoms, and a review of the resources available, current progress, and added value of a forward genetic approach for identification of novel genetic regulators.